Nomenclature proposal for the sonographic description and reporting of soft tissue fillers. (28th August 2019) - Schelke, Leonie W.; Cassuto, Daniel; Velthuis, Peter; Wortsman, Ximena
Abstract: Background: There is a steady increase in publications about the use of ultrasound and filler treatments, written by physicians from different specialties. The terminology used to describe the ultrasound images of fillers is not uniform, making the different articles difficult to compare. Standardization of the descriptions based on their basic sonographic parameters is recommendable. Aims: The purpose of this study is to propose a nomenclature for the sonographic description and reporting of cosmetic fillers. Methods: An assessment of articles indexed for MEDLINE/PubMed and Embed electronic database was conducted; in total of 39 articles could be included. Results: All articles were investigated for their sonographic descriptions of soft tissue fillers. Ten parameters used for describing and monitoring soft tissue fillers were distinguished. Conclusion: The proposed sonographic descriptions for cosmetic fillers may contribute to a better standardization and understanding fillers ultrasound images in the reports or literature.